Efektivitas Penyuluhan Program Digitalisasi pada Industri Rumahan Produksi Keripik Pisang Leunah Lumajang - Fitriyanti, Ade; Bashiroh, Ainin; Anggraini, Arisca Putri; Mushriroh, Rizna Zulfa; Saefudin, Ruli (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: The home-based banana chips industry, Keripik Pisang Leunah, in Lumajang Regency, faces challenges with production efficiency and limited market reach due to its conventional production processes. Through this community service program, the Abdimas team from the Islamic University of Malang aims to implement a digitalization program to improve production efficiency and expand marketing reach, enabling the business to adapt to technological advancements. Methods: The program was implemented using a participatory approach through training and direct mentoring of partners, including training in banana-slicing machines, optimization of social media and marketplace platforms, and digital bookkeeping. Results: The activity showed significant improvements in partners’ managerial and marketing capacities, marked by a 72% increase in the effectiveness of digital media use, a 64% improvement in financial record-keeping efficiency, a 35% increase in income, and a 30% increase in production output. Conclusion: This activity confirms that digitalization can enhance the self-reliance of small enterprises, strengthen the competitiveness of home industries, and contribute to achieving SDGs 1 and 8, which focus on poverty alleviation and sustainable economic growth.